Neurotoxicity De-Risking in Preclinical Drug Discovery - Savić, Miroslav (Archives of Pharmacy, 2022)
The adverse effects of pharmaceuticals on the central or peripheral nervous systems are poorly predicted by the current in vitro and in vivo preclinical studies performed during research and development process. Increasing the predictivity of the preclinical toolbox is a clear need, and would benefit to human volunteers/patients (safer drugs) and pharmaceutical industry (reduced attrition). The NeuroDeRisk Consortium consists of 18 academic, pharmaceutical industry and small and medium enterprise partners within the Innovative Medicines Initiative project (2019-2022). University of Belgrade – Faculty of Pharmacy is the partner that leads the work package devoted to preclinical prediction of mood and cognitive adverse effects. The other two groups of challenging adverse effects tackled by the project are seizures and peripheral neuropathies. By employing a plethora of experimental techniques and numerous pharmaceuticals previously connected with each of major adverse effects examined, the project looks for innovative tools, assays and protocols, which cover in silico, in vitro, in vivo and ex vivo approaches. Besides widening the knowledge on many widely used pharmaceuticals, the major goal of the project is to develop an integrated platform for better risk-assessment in exploratory and regulatory studies in the future.